The Tree of Drawing (diségno, 2020)
"Among Chuang-Tzu’s many skills, he was an expert draftsman. The king asked him to draw a crab. Chuang-Tzu replied that he needed five years, a country house, and twelve servants. Five years later the drawing was still not begun. ‘I need another five years’, said Chuang-Tzu. The king granted them. At the end of these ten years, Chuang-Tzu took up his brush and, in an instant, with a single stroke, he drew a crab, the most perfect crab ever seen”. [Calvino 1988, p. 53]Initially, when we thought up the program of side events with the members of the organising committee at the 41st International Conference of the Performance Disciplines/Congress of the Italian Drawing Union, hosted in2019 by the University of Perugia and dedicated to the two-way relationship established between ar t and drawing, we thought of organising a sculpture exhibition. And, in particular, we imagined exhibiting en plein air, in theUniversity gardens, replicas of three famous contemporary sculptures made with a 3D printer and characterisedby provocative chromatic finishes. Sculptures like Dibuixar l’Espai by Pepe Diaz Azorin, The Man Who Measures theClouds by Jan Fabre and Study of Perspective by Ai Weiwei.